KELIMPAHAN MAKROZOOBENTOS DI PANTAI TANAH MERAH SAMBOJA KUTAI KARTANEGARA KALIMANTAN TIMUR - Brigitha Anjely Agatha Jani; Irma Suryana; Mohammad Sumiran Paputungan; Irwan Ramadhan Ritonga (Jurnal Perikanan Unram, 2024)
Samboja beach is one of the coastal areas in Kutai Kartanegara Regency, which has various fisheries and marine resources such as macrozoobenthos. One of the ecological functions of macrozoobenthos is that it is a biological bioindicator in the waters and transfers energy in the food chain. This study aims to determine the type and abundance of macrozoobenthos, sediment texture type, organic carbon, nitrate and phosphate content, sediment type and abundance of macrozoobenthos at Tanah Merah Beach Samboja. Sediment samples were taken at the surface (0-10 cm) by placing quadrant plots on a 120 m long transect line (50x50 cm²). 50 macrozoobenthos species were found, consisting of Gastropoda, Bivalvia and Schapopoda. Macrozoobenthos abundance ranged from 60 to 268 ind/m2. Sequential ecological indices of diversity included the medium category with high uniformity and low dominance. The sediment texture at points near the coast was sandy loam while towards the sea textured sand. Sediment content in organic carbon ranged from 0.41% to 1.18% (very low), nitrate between 6.63 and 16.69 mg/L (high) and phosphate from 29.01 to 71.27 mg/L (high). There was a positive relationship with a moderate correlation between organic carbon and macrozoobenthos abundance. The relationship between nitrate and macrozoobenthos abundance was a low correlation. In contrast, a positive correlation was found between phosphate and macrozoobenthos abundance. Water quality is still normal and supports the survival of macrozoobenthos.